Unexpected fragmentations of triphosphaferrocene – formation of supramolecular assemblies containing the (1, 2, 4-P3C2Mes2)− ligand12. Issue 14 (10th March 2015) - Heindl, Claudia; Kuntz, Andrea; Peresypkina, Eugenia V.; Virovets, Alexander V.; Zabel, Manfred; Lüdeker, David; Brunklaus, Gunther; Scheer, Manfred
Abstract : An unusual fragmentation of a triphosphaferrocene is observed, when it is reacted with Cu(i ) halides. As a result, a large variety of different monomeric, dimeric and 1D and 2D polymeric coordination compounds are formed. Abstract : While reacting the sterically demanding triphosphaferrocene [Cp*Fe(η 5 -P3 C2 Mes2 )] (1 ) with Cu(i ) halides, the sandwich complex undergoes an unprecedented fragmentation into decamethylferrocene, FeX2 (X = Cl, Br, I) and [P3 C2 Mes2 ] − units. Subsequently, these phospholyl ligands act as versatile, negatively charged building blocks for the formation of supramolecular aggregates representing the monomeric, dimeric and polymeric (1D and 2D) coordination compounds [(P3 C2 Mes2 )2 {Cu7 (CH3 CN)7 (μ4 -X)(μ3 -X)2 (μ-X)}{Cu2 (μ2 -X)2 X}{Cu(CH3 CN)(μ2 -X)}]2 ·6CH3 CN (2 ·6CH3 CN: X = Cl, 3 ·6CH3 CN: X = Br), [(P3 C2 Mes2 )2 {Cu(CH3 CN)}6 (μ-Br)2 (μ3 -Br)2 {Cu(CH3 CN)2 Br}2 ]·CH3 CN (4a ·CH3 CN), [(P3 C2 Mes2 )4 {Cu5 (CH3 CN)5 (μ2 -Br)}{Cu(CH3 CN)2 CuBr2 }2 {Cu(CH3 CN)2 }] n + [CuBr2 ] n − ·2CH3 CN (5 ·2CH3 CN), [(P3 C2 Mes2 ){Cu(CH3 CN)(μ-I)}4 {Cu(CH3 CN)3 }]·0.5C7 H8 ·2.5CH3 CN (6 ·0.5C7 H8 ·2.5CH3 CN), [(P3 C2 Mes2 )Cu7 (CH3 CN)4 (μ4 -I)2 (μ3 -I)2 (μ-I)2 ] x ·2C7 H8 (7 ·2C7 H8 ), [(P3 C2 Mes2 ){Cu(CH3 CN)3 }2 {Cu(μ-I)}6 ]·0.5CH2 Cl2 ·3CH3 CN (8 ·0.5CH2 Cl2 ·3CH3 CN) and [Cp*Fe(CH3 CN)3 ] n + [(P3 C2 Mes2 )2 {Cu(CH3 CN)2 }{Cu(μ-I)}6 ] n − ·0.6CH2 Cl2 (9 ·0.6CH2 Cl2 ) with rather non-typical structural motifs within the large varieties of copper halide chemistry. Besides the X-ray structural analyses the obtained assemblies were also characterized in solution in which they undergo fragmentation and re-aggregation processes.